Respuesta :

Answer:

  • a+b-c = 9.5
  • 10-(a+b) = 0.2
  • b-c+2 = 7.4

Step-by-step explanation:

4)

Given the expression

a+b-c

  • a=4.1
  • b=5.7
  • c=0.3

substituting the values in the expression

a+b-c = 4.1+5.7-0.3

          =  9.8 - 0.3

          = 9.5

5)

Given the expression

10-(a+b)

  • a=4.1
  • b=5.7
  • c=0.3

substituting the values in the expression

10-(a+b) = 10 - (4.1+5.7)

              = 10 - 9.8

              = 0.2

6)

Given the expression

b-c+2

  • a=4.1
  • b=5.7
  • c=0.3

substituting the values in the expression

b-c+2 = 5.7 - 0.3 +2

          = 5.4 + 2

           = 7.4